Uso de fitase microbiana em rações com alimentos vegetais para o piavuçu Leporinus macrocephalus : desempenho, digestibilidade e qualidade de água - Dias, Priscila Gôngora (2007)
It was evaluated the microbial phytase use in diets with vegetables ingredients for Leporinus macrocephalus, on the productive performance, water quality and diets digestibility. The diets (30% PB) were formulated in order to have variations in the presence or absence of phytase (PY) enzyme of integral wheat (IW) and dicalcium phosphate (DP). The treatments were soybean (SM) + DP, SM, SM+PY, IW and IW+PY. To evaluate the productive performance and the water quality, a total of 250 fingerlings (3.20±0.08g), were distributed in 25 tanks (250 L) in a complete randomized design with five treatments and five replications. In the digestibility assay 45 juveniles (184.51±14.55g and 25.16±0.78 cm) were distributed in five glasses (150 L). The fish fed with diets SM, SM+PY and IW presented values of weight gain, feed conversion, protein efficiency index and nitrogen retention that not differed from those with the SM+DP use. The ether extract and phosphorus retention rate of fish were lower with the use of SM+DP in comparison to others treatments. The tanks water with SM+DP use had the highest concentration of orthophosphate in relation to others treatments. SM+PY use than with SM use. It was not observed IW (p>0,05) presence effect on the coefficients of apparent digestibility (CDA) of diets, it was observed the dry matter and gross energy CDA were higher with PY use when compared to the use of diets with only SM. On the other hand the PY use with diets with IW improvement only the dry matter CDA of diets. It was concluded that, for L. macrocephalus fingerlings, it is not necessary to add DP in diets with vegetable base, as well as the PY use promotes improvement in the SM based diets digestibility.